Analysis of seismic pounding between adjacent buildings - Hao, Hong (Engineers Media, 2016)
Seismic poundings between inadequately separated buildings have been observed in most previous major earthquakes. Pounding usually caused local damage around the impacting areas, and in extreme cases, collapse of the building structures. AS1170.4-2007 requires the separation between adjacent buildings to be at least 1% of the building height to avoid seismic pounding. This article presents intensive numerical simulations to examine the adequacy of this specification to preclude seismic pounding between RC frame structures under design earthquake loading defined for Perth, and the effects of pounding, if it occurs, on structural responses. It is found that AS 1170.4-2007 in general provides a conservative approach for determining the required separation distances to avoid pounding. Intensive numerical simulations are also carried out to study the effects of pounding on structural responses. Two adjacent RC frame models of 5-storey and 10-storey with different separation gaps and fundamental period ratios are considered. Impact forces, displacements and shear forces of the two frame structures with or without pounding subjected to ground motions corresponding to different site conditions are calculated. The influences of seismic pounding on frame structures are discussed.